LCTX-F2, a Novel Potentiator of Coagulation Factors From the Spider Venom of Lycosa singoriensis - Li, Pengpeng; Zhang, Zhongzhe; Liao, Qiong; Meng, Er; Mwangi, James; Lai, Ren; Rong, Mingqiang (Frontiers in Pharmacology, 2020)
Spider venoms contain many functional proteins/peptides such as proteinases, serine/cysteine proteinase inhibitors, insecticidal toxins, and ion channel toxins. However, to date, no peptide toxin with procoagulant activities has been identified from spider venom. In this study, a novel toxin LCTX-F2 with coagulation-promoting activity was identified and characterized in the venom of the spider Lycosa singoriensis (L. singoriensis). LCTX-F2 significantly shortened activated partial thromboplastin time (APTT), clotting time, and plasma recalcification time. This toxin directly interacted with several coagulation factors such as FXIIa, kallikrein, thrombin, and FXa and increased their protease activities. In liver bleeding and tail bleeding mouse models, LCTX-F2 significantly decreased the number of blood cells and bleeding time in a dose-dependent manner. At the same dosage, LCTX-F2 exhibited a more significant procoagulant effect than epsilon aminocaproic acid (EACA). Moreover, LCTX-F2 showed no cytotoxic or hemolytic activity against either normal cells or red blood cells. Our results suggested that LCTX-F2 is a potentiator of coagulation factors with the potential for use in the development of procoagulant drugs.